2015
DOI: 10.1007/s13213-015-1115-0
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent tolerance to acetic acid in Dekkera bruxellensis

Abstract: Dekkera bruxellensis-a yeast species associated with wine and beer production-has recently received attention because of its ability to compete with Saccharomyces cerevisiae in distilleries producing fuel ethanol, and due to its resistance to high ethanol and acid levels. The tolerance to acetic acid in 29 strains of D. bruxellensis was investigated by screening growth at different concentrations up to 120 mM at pH 4.5. Different metabolic responses were exhibited in three strains (CBS 98, CBS 2499 and CBS 448… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
1
15
0
1
Order By: Relevance
“…On the other hand, no effect of DSF on cell growth was observed when D. bruxellensis was cultivated in galactose even at MIC dose (Figure b). Galactose metabolism in ammonium‐based medium, as in the case of the present work, is slow and might avoid the overflow to the upper part of the glycolysis, leading to a fully respiratory metabolism and releasing cells from GCR (Moktaduzzaman, Galafassi, Vigentini, et al, ). In addition, glycerol was used as a carbon source that is exclusively metabolized by the mitochondria in a respiratory metabolism.…”
Section: Resultsmentioning
confidence: 72%
“…On the other hand, no effect of DSF on cell growth was observed when D. bruxellensis was cultivated in galactose even at MIC dose (Figure b). Galactose metabolism in ammonium‐based medium, as in the case of the present work, is slow and might avoid the overflow to the upper part of the glycolysis, leading to a fully respiratory metabolism and releasing cells from GCR (Moktaduzzaman, Galafassi, Vigentini, et al, ). In addition, glycerol was used as a carbon source that is exclusively metabolized by the mitochondria in a respiratory metabolism.…”
Section: Resultsmentioning
confidence: 72%
“…1); these growth kinetics were reproducible. In contrast, we noticed that the culture of strain CBS 98, which was one of the less-tolerant strains (30), behaved in a less reproducible way, with adaptive phases lasting 70 to 300 h (see Fig. 1 for an example); additionally, some cultures did not grow at all.…”
Section: Resultsmentioning
confidence: 88%
“…In particular, the cultivation in liquid medium under aerobic conditions revealed that also the growth of the most-tolerant strain, CBS 4482, was negatively affected by the presence of 120 mM acetic acid. It caused a reduced growth rate, a reduced specific glucose consumption rate, and a reduced specific ethanol production rate (30). In a new set of experiments, strain CBS 4482 showed an initial adaptive phase that lasted approximately 60 h and a subsequent faster exponential-growth phase (growth rate, 0.06 h Ϫ1 ) during shake flask cultivation in liquid glucose-based medium containing 120 mM acetic acid at pH 4.5 (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In this study, a more detailed analysis has been carried out to investigate the short-term ethanol response of both parental and engineered strains. A FTIR-based assay, already employed as a powerful technique for ecotoxicological assessments [28][29][30], was carried out to estimate the type and extent of perturbations induced by ethanol stress on both parental and recombinant yeast strains. Ethanol levels were specifically chosen based on the alcohol concentrations typical of the bioethanol industry [18,22].…”
Section: Ftir Fingerprints Under Ethanol Stressmentioning
confidence: 99%